Employment protection legislation, adjustment costs and cross-country differences in cost behavior - Banker, Rajiv D.; Byzalov, Dmitri; Chen, Lei (Tony) (Journal of accounting & economics, 2013)
Central to the economic theory of sticky costs is the proposition that managers consider adjustment costs when changing resource levels. We test this proposition using employment protection legislation (EPL) provisions in different countries as a proxy for labor adjustment costs. Using a large sample of firms in 19 OECD countries during 1990–2008, we find that the degree of cost stickiness at the firm level varies with the strictness of the country-level EPL provisions. This finding supports the theory that cost stickiness reflects the deliberate resource commitment decisions of managers in the presence of adjustment costs. ► We develop and test the economic theory that can explain the pervasive empirical findings of sticky costs. ► If the theory holds, higher adjustment costs should increase stickiness. ► Employment protection legislation (EPL) strictness is a reliable empirical proxy for labor adjustment costs. ► In cross-country analysis for 19 OECD countries, stricter EPL is associated with higher stickiness, supporting the theory.